Exploring the Ancestral Mechanisms of Regulation of Horizontally Acquired Nitrogenases - Pascuan, Cecilia Gabriela (2015)
The vast majority of Pseudomonas species areunable to fix atmospheric nitrogen. Although severalstudies have demonstrated that some strains belonging tothe genus Pseudomonas sensu stricto do have the ability tofix nitrogen by the expression of horizontally acquirednitrogenase, little is known about the mechanisms ofnitrogenase adaptation to the new bacterial host. Recently,we transferred the nitrogen fixation island from Pseudomonasstutzeri A1501 to the non-nitrogen-fixing bacteriumPseudomonas protegens Pf-5, and interestingly, theresulting recombinant strain Pf-5 X940 showed anuncommon phenotype of constitutive nitrogenase activity.Here, we integrated evolutionary and functional approachesto elucidate this unusual phenotype. Phylogeneticanalysis showed that polyhydroxybutyrate (PHB) biosynthesisgenes from natural nitrogen-fixing Pseudomonasstrains have been acquired by horizontal transfer. Contraryto Pf-5 X940, its derived PHB-producing strain Pf-5 X940-PHB exhibited the inhibition of nitrogenase activity undernitrogen-excess conditions, and displayed the typicalswitch-on phenotype observed in natural nitrogen-fixingstrains after nitrogen deficiency. This indicates a competitionbetween PHB production and nitrogen fixation.Therefore, we propose that horizontal transfer of PHBbiosynthesis genes could be an ancestral mechanism ofregulation of horizontally acquired nitrogenases in thegenus Pseudomonas.